2018
DOI: 10.3892/ol.2018.7975
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic mimicry in bladder cancer and its association with the aberrant expression of ZEB1

Abstract: Abstract. The aim of the present study was to investigate the associations between vasculogenic mimicry (VM) and zinc finger E-box binding homeobox 1 (ZEB1) in bladder cancer. VM structure and ZEB1 expression were analyzed by cluster of differentiation 34/periodic acid Schiff (PAS) double staining and immunohistochemical staining in 135 specimens from patients with bladder cancer, and a further 12 specimens from normal bladder tissues. Three-dimensional (3-D) culture was used to detect VM formation in the blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 24 publications
(36 reference statements)
1
22
1
Order By: Relevance
“…The ZEB transcription factor family acts by binding to the cadherin promoter region 39,40. ZEB1 promotes the formation of angiogenesis and induces EMT in bladder cancer 41. The transformation of epithelial cells into mesenchymal cells is accompanied by an increase in cancer stemness, metastatic ability, and drug resistance 42.…”
Section: Discussionmentioning
confidence: 99%
“…The ZEB transcription factor family acts by binding to the cadherin promoter region 39,40. ZEB1 promotes the formation of angiogenesis and induces EMT in bladder cancer 41. The transformation of epithelial cells into mesenchymal cells is accompanied by an increase in cancer stemness, metastatic ability, and drug resistance 42.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that ZEB1 was significantly overexpressed in bladder cancer tissues compared to normal healthy adjacent tissues [36]. Li et al [37] reported that ZEB1 was significantly overexpressed in bladder cancers compared to normal tissues, and played a crucial role during VM formation, and was closely associated with invasion, metastasis and poor prognosis of malignant tumors [38, 39]. Transmembrane protein 100 (TMEM100), located at 17q32, was first identified as a transcript in the mouse genome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies postulate the presence of VM based on a luminal space in a carcinoma cross-section, however no PAS+ border is present (16). Similarly, weak PAS staining always leaves the doubt of whether a membrane is present or the structure is in fact a blood pool (1720). In contrast, several reports from the group of Sun and colleagues clearly demonstrate the presence of PAS+/CD31- structures that contain RBCs in both Hepatocarcinoma and Gastro Intestinal Stromal Tumor (GIST) patients (14, 21).…”
Section: Vm In the Clinic: What Is The Evidence In Cancer Patients?mentioning
confidence: 99%
“…The literature on in vitro VM models contains several attempts for a quantification method. Such studies have employed a variety of methods including: tubule length, number of structures, tubular structure connections, or PAS+ levels (16, 17, 6062). However, as explained above most studies have failed to demonstrate these tubular structures are indeed functional (i.e., have a fluid-conducting lumen) therefore the validity of these methods remains questionable.…”
Section: Vm Quantification: Is Pas a Good Marker?mentioning
confidence: 99%